Effects of dental occlusion on body sway, upper body muscle activity and shooting performance in pistol shooters - Dias. A. A.; Redinha, L. A.; Silva, L. M.; Pezarat-Correia, P. C. (Applied Bionics and Biomechanics, 2018)
Occlusal splints, to some extent, have been related to reduced body sway in a static position and increased muscle activity in the upper limbs. However, how dental occlusion status affects sports performance remains unclear. Here, we investigated whether occlusal splints that reposition the temporomandibular joint (TMJ) influenced body posture, muscle activity, and performance in 10-meter pistol shooters. Thirteen national-level male shooters (age = 38.8 ± 10.9 yrs) were recruited for this study, and cleared of any cervical pathology. An occlusal splint (OS) and a placebo splint (PS) were fabricated for each of the subjects, with the mandibular and maxillary position verified by an expert dentist, with the aid of an adjustable articulator. Surface electromyography (EMG) was assessed in the upper limb that holds the pistol while the subjects were standing on a force platform. Subjects performed two series of 10 shots for each of the three experimental conditions (OS, PS, N (no splint)) in randomized order, with the mandible in a rest position. Results revealed similar centre of pressure (COP) parameters in all conditions, despite a reduction in the average oscillation area caused by the OS. There were also no significant differences in EMG activity between conditions in the five upper limb muscles monitored. Consistent with this, shooting performance was similar in all conditions, despite a reduction in shot dispersion in subjects using OS. Thus, changes in dental occlusion status induced by OS do not affect body posture, upper limb EMG muscle activity, or shot performance in healthy male pistol shooters